2013
DOI: 10.1080/17457300.2013.826698
|View full text |Cite
|
Sign up to set email alerts
|

Seat-belt use still low in Kuwait: self-reported driving behaviours among adult drivers

Abstract: Kuwait mandated seat-belt use by drivers in 1976 and by front seat passengers in 1994. The study objectives were to identify and estimate current factors associated with seat-belt use and levels of potentially unsafe driving behaviours in Kuwait. In 2010, 741 adults were surveyed regarding driving habits and history. Only 41.6% of drivers reported always using a seat belt. Front seat passenger belt use was more common (30.5%) than rear seat belt use (6.5%). Distracted driving behaviours were common, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 33 publications
2
10
2
Order By: Relevance
“…This includes speeding, responsible for about 50% of RTI deaths globally [ 21 ] and also a significant factor in the EMR region. In addition, local studies found a seatbelt non-compliance rate ranging from 48% [ 22 ] to 82% [ 23 ] in the total road traffic crashes and 58% non-compliance when self-reported [ 24 ]. This is despite the fact that the majority of the EMR countries reporting the existence of national legislation in national speed limits, drink-driving, motorcycle helmet, seat-belt, drug-influenced driving and mobile phone use (distracted driving) laws [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…This includes speeding, responsible for about 50% of RTI deaths globally [ 21 ] and also a significant factor in the EMR region. In addition, local studies found a seatbelt non-compliance rate ranging from 48% [ 22 ] to 82% [ 23 ] in the total road traffic crashes and 58% non-compliance when self-reported [ 24 ]. This is despite the fact that the majority of the EMR countries reporting the existence of national legislation in national speed limits, drink-driving, motorcycle helmet, seat-belt, drug-influenced driving and mobile phone use (distracted driving) laws [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research also highlights young people's behavior, including low seat belt compliance, eating, drinking, and using mobile phones while driving, speeding and reckless driving, driving without a license, and violating local traffic laws, as documented in studies from Kuwait [79], Oman [80], Qatar [81,82], Saudi Arabia [83,84], and the UAE [85e87]. A national study among students in Oman found that 33% had driven without a license and 34% said they liked to speed [88,89].…”
Section: Transport Injuriesmentioning
confidence: 97%
“…Despite these obvious and tangible public health advantages, seatbelt use while driving is still very low (48%) in GCC countries (Abbas et al 2011a ), even lower (27.2%) in Saudi Arabia (Bendak 2007 ), and other countries including Iran (33%) (Mohammadi 2011 ), located in WHO Eastern Mediterranean Region as oppose to developed countries (Bendak 2005 ). Furthermore, a very high proportion of drivers use the seatbelt while driving in USA (87%), UK (90%), Australia (97%) as compared to high income developing GCC countries including Qatar (73%) (Mahfoud et al 2015 ), Kuwait (42%) (Raman et al 2014 ), UAE (29%) (Barss et al 2008 ) and Bahrain (20%) (WHO 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Noncompliance with mandatory seatbelt-use law is a significant contributory factor in occupants’ injuries and/ or death rates (Abbas et al 2011b ). In Kuwait, mandatory seatbelt use law for drivers was enacted 1976 and for all front seat passengers in 1994 (Raman et al 2014 ; Koushki and Bustan 2006 ). Despite the implementation of seatbelt law while driving, over the years the prevalence of noncompliance among the drivers remained nearly constant as 45% in 1996 (Koushki et al 1996 ), and 42% in 2014 (Raman et al 2014 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation